Membangun Media Pembelajaran Interaktif Mata Pelajaran Microsoft Office Menggunakan Adobe Animate 2021 - Trisna; Muhajir; Suryanto (Jurnal Informatika dan Komputer (JIK), 2022)
The quality of education requires efficient breakthroughs, both in learning innovation, curriculum development and supporting existing infrastructure facilities, so that with this, education and learning will be carried out effectively. In accordance with the mandate of Government Regulation Number 32 of 2013 concerning National Education Standards, one of the standards that must be developed is process standards. Process standards are national education standards related to implementation in educational units to achieve graduate competence. Electronic Learning is learning that uses the help of computer systems or hardware and software, so that it focuses more on the learning process and computer equipment only as a medium. E-learning is a relatively new information-based learning. As for the smooth teaching and learning process, teachers can use assistive media, assistive media can be in the form of models, textbooks, transparency films, video cassettes, computer-based media and others. In the teaching and learning process to be effective, it requires a method that is in accordance with the character of the students, the subjects delivered, the atmosphere and supporting infrastructure. The method used is problem formulation, data collection, problem identification and research results. This research produces an Interactive Learning Media Application that helps students' understanding in the teaching and learning process, in order to create efficient and educational learning. This learning media was created using adobe animate 2021 with a menu display of video menu materials and practice questions, as for the results of this study, an application of learning media with the Apk format. Android using adobe animate 2021